The Development of Android-Based TMC (Thermochemical) Learning Media Assisted by Smart Apps Creator to Improve Students’ Learning Outcomes - Mellyta Uliyandari; Sutarno Sutarno (SEJ (Science Education Journal), 2023)
One form of technological development in field of education is the creation of various Android-based learning media. The purpose of this study was to develop Android-based Thermochemical (TMC) learning media assisted by Smart Apps Creator to improve student s’ learning outcomes in thermochemical material. The development in this study was carried out with a 4-D design, define, design, develop, and disseminate. The results of the study show that TMC learning media is very feasible to use based on the validation results two validators,namely material experts and media experts. The learning media validation score by material experts was 75 in "Very Eligible" category, while the validation results by media experts were 56 in "Very Eligible" category. The results of the media feasibility assessment by students showed that they were in the "Very feasible" category with conversion value of 35.32. Student responses to the media are in the agree category with conversion value of 4.21. Student learning outcomes after using the TMC learning media also experienced an increase based on a comparison between student pretest and posttest scores. The average score of students' pretest before using TMC media was 54.46 while the average posttest score of students after using TMC media was 82.74. The results of the student pretest and posttest gain test have score of 0.62 in the "Moderate" category.